PULBIN PEDIA: an Interactive dynamic web as a bioconservation learning resource for preservice science teacher - Natadiwijaya, Ismail Fikri; Yuliana, Eva; Sugianto, Sugianto; Rachman, Dwi Fauzi; Subkhi, Nur; Luzyawati, Lesy (International Journal of Mathematics and Sciences Education, 2024)
Bioconservation is an interdisciplinary science whose purpose is to encourage the development of theory and application in conservation areas. Biawak Island is one of the leading conservation areas in the Indramayu district, therefore Bioconservation learning should be done directly on Biawak Island. In practice, studying Bioconservation directly on Biawak Island is difficult because of the long distance and expensive access to this place. Based on these problems, an interactive dynamic web in the form of a digital encyclopedia is a solution for the problem. Digital encyclopedia named “PULBIN PEDIA”. That was implemented in one of the private universities in West Java. The design used is Descriptive Qualitative. A qualitative approach is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. This research was conducted on 24 students who were taking the course of Bioconservation in the academic years of 2023/2024.  The results of the analysis from observations found that PULBIN PEDIA is an interactive and dynamic media and can be implemented as an integrated learning resource in Bioconservation lectures because it contains complete and accurate information regarding the location, origin of the name, management, conservation activities, conservation actors and biodiversity on Biawak Island. PULBIN PEDIA also can be implemented as a learning resource in lectures that apply problem-based learning strategies where students can find 3 (three) conservation problems, investigate components that have been conserved, and formulate solutions on how to preserve Biawak Island.